FGF21 inhibits invasion and metastasis via IL-17A-Notch in pancreatic ductal adenocarcinoma - Li, Fangdan; Zheng, Panchun; Li, Xiongwu; Yang, Yaying; Zhou, Hangyu; Li, Linjun (Frontiers in Oncology, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) demonstrates characteristic histopathological features marked by abundant inflammatory cell infiltration and the formation of dense fibrous stromal capsules, which contribute to its aggressive metastatic potential. Although Fibroblast Growth Factor 21(FGF21) exhibits pancreatic anti-inflammatory properties, its expression becomes markedly downregulated in PDAC. The present research explores the inhibitory effects of FGF21 on PDAC progression within inflammatory microenvironments, with particular focus on delineating the involved signaling pathways and molecular interactions.MethodsWe detected FGF21 expression in human PDAC specimens and analyzed its relationship with various clinicopathological features. For in vitro studies, an inflammatory microenvironment of PDAC cell lines was modeled by Lipopolysaccharide (LPS) stimulation and Transwell assays were used to detect the effects of recombinant FGF21 on invasion and migration. In vivo, a splenic-liver metastasis model was established in nude mice and liver metastases were monitored by imaging following intraperitoneal administration of LPS or/and FGF21. Signaling pathways of FGF21 in PDAC cell lines were identified through transcriptome sequencing and bioinformatics analysis, with key components validated by RT-PCR, Western blot and ELISA.ResultsLow expression of FGF21 in PDAC patients is associated with higher TNM stages and increased rates of lymph node metastasis, vascular invasion, and tumor recurrence compared to high expression of FGF21.In vitro and in vivo studies revealed FGF21 significantly suppressed migration and invasion in cultured PDAC cell lines and reduced hepatic metastasis in murine models after LPS treatment. FGF21 downregulated key Notch signaling components (HES1, HES2, RBPJ, ZEB1, Notch1, Notch3) while concurrently attenuated Interleukin-17A (IL-17A) production. After IL-17A addition to PDAC cell lines, the inhibitory effect of FGF21 on the Notch signaling pathway was significantly reduced.ConclusionFGF21 suppresses invasion and metastasis in PDAC by inhibiting the IL-17A-Notch signaling axis, which reveals a novel therapeutic strategy for this malignancy.